Adrenal insufficiency in patients with Prader-Willi syndrome - Kusz, Marcin Jerzy; Gawlik, Aneta Monika (Frontiers in Endocrinology, 2022)
The generalized dysfunction of the hypothalamic-pituitary axis in patients with Prader-Willi syndrome (PWS) is the most likely cause of hypogonadism, inadequate growth hormone secretion, excessive appetite and associated obesity, impaired body temperature regulation, and hypothyroidism. The syndrome is also related to an increased risk of central adrenal insufficiency, although its prevalence remains unknown. The results of the studies in which different methods of pharmacological stimulation were used do not provide conclusive outcomes. As a result, there are no clear guidelines with regard to diagnosis, prevention, or long-term care when adrenal insufficiency is suspected or diagnosed in patients with PWS. Currently, most patients with PWS are treated with recombinant human growth hormone (rhGH). It has been confirmed that rhGH therapy has a positive effect on growth, body composition, body mass index (BMI), and potentially on psychomotor development in children with PWS. Additionally, rhGH may reduce the conversion of cortisone to cortisol through inhibition of 11β-hydroxysteroid dehydrogenase type 1. However, its influence on basal adrenal function and adrenal stress response remains unexplained in children with PWS. This paper reviews the literature related to the hypothalamic-pituitary-adrenal axis dysfunction in the PWS patient population. The literature review was based on the available papers published in the PubMed database between 1963 and June 2021. The search criteria used in the Medical Subject Headings (MeSH) were as follows: “Prader-Willi” [All Fields] AND (“adrenal glands”[MeSH Terms] OR (“adrenal”[All Fields] AND “glands”[All Fields]) OR “adrenal glands”[All Fields] OR “adrenals”[All Fields] OR “adrenalitis”[All Fields] OR “adrenally”[All Fields] OR “epinephrine”[MeSH Terms] OR “epinephrine”[All Fields] OR “adrenal” [All Fields])”. Only original papers in English were analyzed. Case reports or literature reviews were not included in the review. Based on the criteria, 63 potentially relevant papers were identified. After analyzing the titles, abstracts and whole papers, nine articles that met the criteria were included in the detailed analysis.